Pengaruh Pemahaman Perpajakan Tentang Tarif Dan Sanksi Pajak Terhadap Persepsi Mahasiswa Mengenai Penggelapan Perpajakan - Annisa Aulia Rahma; Sri Nirmala Sari; Veronika Sari Den Ka (JURNAL PABEAN : PERPAJAKAN BISNIS EKONOMI AKUNTANSI MANAJEMEN, 2021)
This study aims to examine the effect of tax penalties and rates on the perception of tax evasion among Bosowa Polytechnic Students. The results of this study are the results of data processing tests using the SPSS version 25 data processing program to determine  the effect of understanding tax penalties and rates on the perception of tax evasion. The research technique used in this study is a questionnaire. The questionnaire is a data collection technique by distributing or providing several lists of statements either on a sheet of paper or in the form of a link that will be answered by the respondents in the hope that they will give a response to some of the questions made by the researcher.The research technique that will be used in this research is questionnaire. it can be seen that based on the results of the T test (partial), it was found that the understanding of sanctions on the perception of tax evasion had a significant effect. Based on the results of the T test (partial) analysis, it was also found that the understanding of tax rates on the perception of tax evasion had a significant effect. And based on the results of the F test analysis test or the influence between the two variables, it can be concluded that the two independent variables have a significant effect on the dependent variable.Keywords: Tax Sanctions, Tax Rates, Tax Evasion